PENGARUH PROMOSI, LAYANAN KONSUMEN DAN BRAND BERLOGO HALAL TERHADAP KEPUTUSAN PEMBELIAN KOPI JANGKAT - Gion Ramadhan; Yudhi Novriansyah; Supriyati Supriyati (Ensiklopedia of Journal, 2022)
This study aims to see whether there is an effect of Promotion, Consumer Service and Brand with Halal Logo on the Purchase Decision of Jangkat Coffee in Bangko District, Merangin Regency, Jambi Province. From a total population of 420 people and 42 people were used as samples of this study using the Random Sampling technique. The results of this study indicate that from the results of the f-test there is a sig value. 0.000 < 0.05 variable promotion, consumer service, and brand with the halal logo have a positive influence on the decision to purchase Term coffee. From the results of the t-test, it is stated that the promotion has a sig value. 0.00 < 1.68595 which means that it has a positive effect on purchasing decisions, customer service has a sig value. 0.100 < 1.68595 which means that consumer service has a significant positive influence and the brand with the halal logo has a sig value. 0.298 < 1.68595, which means that the brand with the halal logo has a positive effect on the decision to purchase anchor coffee. This finding shows that to determine consumer purchasing decisions in purchasing products requires good promotion, as well as providing excellent customer service, and a brand with a halal logo as a guarantee that a product is safe for use or consumption.